Is Photocatalysis the Next Technology to Produce Green Hydrogen to Enable the Net Zero Emissions Goal?. Issue 3 (16th December 2022) - Isaacs, Mark; Garcia‐Navarro, Julio; Ong, Wee‐Jun; Jiménez‐Calvo, Pablo
Abstract: Energy security concerns require novel greener and more sustainable processes, and Paris Agreement goals have put in motion several measures aligned with the 2050 roadmap strategies and net zero emission goals. Renewable energies are a promising alternative to existing infrastructures, with solar energy one of the most appealing due to its use of the overabundant natural source of energy. Photocatalysis as a simple heterogeneous surface catalytic reaction is well placed to enter the realm of scaling up processes for wide scale implementation. Inspired by natural photosynthesis, artificial water splitting's beauty lies in its simplicity, requiring only light, a catalyst, and water. The bottlenecks to producing a high volume of hydrogen  are several: Reactors with efficient photonic/mass/heat profiles, multifunctional efficient solar‐driven catalysts, and proliferation of pilot devices. Three case studies, developed in Japan, Spain, and France are showcased to emphasize efforts on a pilot and large‐scale examples. In order for solar‐assisted photocatalytic H2 to mature as a solution, the aforementioned bottlenecks must be overcome for the field to advance its technology readiness level, assess the capital expenditure, and enter the market. Abstract : The 2050 roadmap strategies and net zero emission goals are made possible through the adoption of novel greener and more sustainable processes. In this regard, exploiting solar irradiation (a plentiful energy source) is advantageous for developing green hydrogen technologies. Photocatalytic devices are suited for large‐scale plants proliferation. Three case studies from France, Spain, and Japan are presented.